2018
DOI: 10.1021/acsbiomaterials.8b00029
|View full text |Cite
|
Sign up to set email alerts
|

Biocompatible and Stable GO-Coated Fe3O4 Nanocomposite: A Robust Drug Delivery Carrier for Simultaneous Tumor MR Imaging and Targeted Therapy

Abstract: Combined targeted drug delivery and sustained drug release, through the application of nanomedicine, show great potential in cancer therapy and diagnostics. Systems based on folic acid conjugated with graphene oxide-based magnetic nanoparticles (NPs) show distinct advantages for such chemotherapeutic applications. Herein, we prepared FA-Fe3O4@nGO-DOX magnetic nanoparticles (MNPs) with a uniform size distribution based on nanoscale graphene oxide (nGO) encapsulated Fe3O4, which was conjugated with folic acid (F… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
34
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 53 publications
(35 citation statements)
references
References 63 publications
0
34
0
1
Order By: Relevance
“…In addition, it is difficult to monitor the drug pharmacokinetic and therapeutic effect due to the lack of powerful imaging modalities, though magnetic resonance imaging (MRI) has witnessed one of the most powerful techniques in the field of prostate cancer imaging [4]. e improvement in multifunctional nanoparticle technology for combined targeted drug delivery and tumor imaging provides new opportunities to overcome these obstacles [5]. It has been reported that stable GO-coated Fe3O4 nanocomposites are successfully used as a robust drug delivery carrier for simultaneous tumor MR imaging and targeted therapy [5].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, it is difficult to monitor the drug pharmacokinetic and therapeutic effect due to the lack of powerful imaging modalities, though magnetic resonance imaging (MRI) has witnessed one of the most powerful techniques in the field of prostate cancer imaging [4]. e improvement in multifunctional nanoparticle technology for combined targeted drug delivery and tumor imaging provides new opportunities to overcome these obstacles [5]. It has been reported that stable GO-coated Fe3O4 nanocomposites are successfully used as a robust drug delivery carrier for simultaneous tumor MR imaging and targeted therapy [5].…”
Section: Introductionmentioning
confidence: 99%
“…e improvement in multifunctional nanoparticle technology for combined targeted drug delivery and tumor imaging provides new opportunities to overcome these obstacles [5]. It has been reported that stable GO-coated Fe3O4 nanocomposites are successfully used as a robust drug delivery carrier for simultaneous tumor MR imaging and targeted therapy [5]. Moreover, the innovative contrast agents for tumor imaging such as ultrasmall bimetallic bovine serum albumin-directed gold-silver (Au-Ag@BSA) nanoparticles have attracted significant attention for potential applications in the fields of multifunctional nanomedicine [6].…”
Section: Introductionmentioning
confidence: 99%
“…Au and Ag decorated graphene-based materials were also used for Raman imaging [145]. Li et al prepared folic acid-Fe 3 O 4 @nGO-DOX using nGO encapsulated Fe 3 O 4 , which is very effective for simultaneous tumor MRI imaging and target therapy [173].…”
Section: Nanoparticle Functionalized Graphene-based Materialsmentioning
confidence: 99%
“…This multifunctional cancer therapy platform has achieved superior therapeutic efficacy for in vitro and in vivo cancer therapy. using nGO encapsulated Fe3O4, which is very effective for simultaneous tumor MRI imaging and target therapy [173].…”
Section: Nanoparticle Functionalized Graphene-based Materialsmentioning
confidence: 99%
“…A recent study by Mantha et al reported that magnetite nanoparticles can be conjugated to anesthetic drugs such as Ropovacaine to deliver site-specific anesthesia [ 19 ]. Furthermore, iron oxide nanoparticles have also been employed as a drug delivery carrier [ 20 ]. However, as the nanoparticles are not coated with any biocompatible material, the cytotoxic effects of nanoparticles alone cannot be avoided.…”
Section: Introductionmentioning
confidence: 99%